Toward a better understanding of the health impairment process. Types of demand and burnout component matter - Baka, Lukasz; Prusik, Monika; Jasielska, Dorota (Frontiers in Psychiatry, 2023)
The aim of the study was to better understand the health impairment process, postulated by Job Demands-Resources (JD-R) model. Previous studies on the process have not clearly explained which types of job demands (challenge vs. hindrance) lead to depression and which burnout component (exhaustion or disengagement from work) mediates job demands - depression link. The direct and indirect (mediated via exhaustion and disengagement from work) effects of challenge and hindrance stressors (included 6 different demands) on depression were investigated in this one-year cross-lagged study. Data were collected among 752 social service workers in Poland. Structural equation modelling confirmed a slightly different effects of challenge and hindrance stressors (T1) on the two components of job burnout (T2) and depression (T2). Hindrance (but not challenge) stressors were related to high depression. Hindrance stressors intensified exhaustion and disengagement from work, while challenge stressors were only associated with high exhaustion. Exhaustion (but not disengagement from work) was related to depression. These findings support the mediation function of burnout in the health impairment process but only in relation to exhaustion. They also showed that the challenge–hindrance distinction is justified also in the JD-R model. The implications for theory and research on the mental health of employees, as well as for human management practice are discussed.